2015
DOI: 10.1007/s00426-015-0658-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of egocentric and allocentric spatial representations from childhood to elderly age

Abstract: Spatial reference frames are fundamental to represent the position of objects or places. Although research has reported changes in spatial memory abilities during childhood and elderly age, no study has assessed reference frames processing during the entire lifespan using the same task. Here, we aimed at providing some preliminary data on the capacity to process reference frames in 283 healthy participants from 6 to 89 years of age. A spatial memory task requiring egocentric/allocentric verbal judgments about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
77
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 103 publications
11
77
0
3
Order By: Relevance
“…The studies showed that TD children learn to form egocentric representations by 2-5 years old, and can even use environmental information, such as the shape of a room (Hermer and Spelke, 1994;Newcombe et al, 1998). At around 6 years of age their mental representations can become view-independent, showing the children's ability to use the structural features of an environment to infer target locations (e.g., Nardini et al, 2008Nardini et al, , 2009Ruggiero et al, 2016).…”
Section: Path Learning With Actual Movesmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies showed that TD children learn to form egocentric representations by 2-5 years old, and can even use environmental information, such as the shape of a room (Hermer and Spelke, 1994;Newcombe et al, 1998). At around 6 years of age their mental representations can become view-independent, showing the children's ability to use the structural features of an environment to infer target locations (e.g., Nardini et al, 2008Nardini et al, , 2009Ruggiero et al, 2016).…”
Section: Path Learning With Actual Movesmentioning
confidence: 99%
“…It might be that the TD children's performance is better in the Observation condition than in the Map condition, however. This would be due to their retaining a preference for egocentric representations (Siegel and White, 1975;Ruggiero et al, 2016);…”
Section: Rationale and Aims Of The Studymentioning
confidence: 99%
“…A key difference between the two perspectives is that in the route perspective, the elements, for example, landmarks, are represented sequentially, whereas in the survey perspective, they are represented simultaneously along with information about their relative spatial positions. TD children can develop spatial representations from an allocentric view – that is, they can acquire survey knowledge – by 5 years of age (Bullens, Igloi, Berthoz, Postma, & Rondi‐Reig, ; Ruggiero, D'Errico, & Iachini, ), and most individuals with DS only reach a mental age of about 5 years (Dykens et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…These age-54 related shifts in strategy use have been interpreted in relation to the slow maturation (in 55 development) and early deterioration (in aging) of the brain areas involved in spatial navigation (e.g. 56 the hippocampus or frontal areas [13][14][15][16][17] ). 57An alternative hypothesis has been proposed recently.…”
mentioning
confidence: 99%